Phonetic similarity between Chinese and Spanish fricatives - Liu, Zhao; Machuca, María Jesús (Círculo de Lingüística Aplicada a la Comunicación, 2025)
In contrastive studies between languages, phonemes are typically compared to determine whether they are identical. However, only a handful of studies have examined the acoustic parameters of these phonemes to reach such an end. This paper compares and evaluates the acoustic properties of phonemes from two languages that have some similar phonemes. The languages under study are Mandarin Chinese and Spanish. Two groups of participants, native Chinese speakers and native Spanish speakers read texts containing fricatives in both languages. Comparisons were made between groups and languages. The results show that even though these two languages may share some similar fricatives, the acoustic parameters may present different values. In addition,Chinese speakers have established identical phonetic categories for both languages, whereas Spanish speakers have yet to accomplish this.
Keywords: phonetic similarity; fricatives; Chinese; Spanish